Is there an association between cardiorespiratory fitness and stage of illness in psychotic disorders? A systematic review and meta‐analysis. (14th November 2019) - Heggelund, J.; Vancampfort, D.; Tacchi, M. J.; Morken, G.; Scott, J.
Abstract : Background: Clinical staging models describe where an individual exists on a continuum from asymptomatic at‐risk states (Stage 0) through to established late‐stage disease (Stage 4). We applied this framework to systematically assess evidence for any associations between objectively assessed cardiorespiratory fitness (CRF) and stage of psychosis. Method: Nine electronic databases were searched for relevant publications from inception until October 31, 2019. Pooled effect sizes (Hedges' g and 95% confidence intervals (95% CI)) were estimated for differences in CRF for studies that reported mean oxygen uptake (max, peak, or predicted VO2 in ml/kg/min). Results: Thirty‐eight studies were eligible. Findings indicated that suboptimal CRF can be present at Stages 0 and 1. Meta‐analyses of 22 studies demonstrated that CRF was significantly reduced in individuals classified between Stages 1 and 4 compared with matched or general population controls ( g  = −0.93; 95% CI −1.14, −0.71). Mean VO2 was decreased by 28% in Stage 4 compared with Stage 1 (34.1 vs. 24.66 ml/kg/min); the largest effect size for CRF reduction was reported between Stages 2 and 3 ( g  = −1.16; 95% CI −1.31, −1.03). Conclusions: Although not identifying direct causal links between clinical stage and CRF, using this framework may enhance understanding of co‐associations between mental and physical health markers across the entire spectrum of psychosis. Limitations include lack of research on CRF in Stages 0 and 1 alongside problems determining stage in some studies. However, impaired CRF is reported in emerging psychosis, supporting calls that early intervention programmes should address both mental and physical wellbeing.